Characterization, Genetic Analyses, and Identification of QTLs Conferring Metabolic Resistance to a 4-Hydroxyphenylpyruvate Dioxygenase Inhibitor in Sorghum (Sorghum bicolor) - Pandian, Balaji Aravindhan; Varanasi, Aruna; Vennapusa, Amaranatha R.; Sathishraj, Rajendran; Lin, Guifang; Zhao, Mingxia; Tunnell, Madison; Tesso, Tesfaye; Liu, Sanzhen; Prasad, P. V. Vara; Jugulam, Mithila (Frontiers in Plant Science, 2020)
Postemergence grass weed control continues to be a major challenge in grain sorghum [Sorghum bicolor (L.) Moench], primarily due to lack of herbicide options registered for use in this crop. The development of herbicide-resistant sorghum technology to facilitate broad-spectrum postemergence weed control can be an economical and viable solution. The 4- hydroxyphenylpyruvate dioxygenase-inhibitor herbicides (e.g., mesotrione or tembotrione) can control broad-spectrum of weeds including grasses, which, however, is not registered for postemergence application in sorghum due to crop injury. In this study, we identified two tembotrione-resistant sorghum genotypes (G-200, G-350) and one susceptible genotype (S-1) by screening 317 sorghum lines from a sorghum association panel (SAP). These tembotrione-resistant and -susceptible genotypes were evaluated in a tembotrione dose-response (0, 5.75, 11.5, 23, 46, 92 (label recommended dose), 184, 368, 736 g ai ha-1) assay. Compared to S-1, the genotypes G-200 and G-350 exhibited 10- and 7-fold more resistance to tembotrione, respectively. To understand the inheritance of tembotrione-resistant trait, reciprocal crosses were performed using S-1 and G-200 or G-350 to generate F1 and F2 progeny. The F1 and F2 progeny were assessed for their response to tembotrione treatment. Genetic analyses of the F1 and F2 progeny demonstrated that the tembotrione resistance in G-200 and G-350 is a partially-dominant polygenic trait. Furthermore, cytochrome P450 (CYP)-inhibitor assay using malathion and piperonyl butoxide suggested possible CYP-mediated metabolism of tembotrione in G-200 and G-350. Genotype-by-sequencing based quantitative trait loci (QTL) mapping revealed QTLs associated with tembotrione resistance in G-200 and G-350 genotypes Overall, the genotypes G-200 and G-350 confer a high level of metabolic resistance to tembotrione and controlled by a polygenic trait. There is an enormous potential to introgress the tembotrione resistance into breeding lines to develop agronomically desirable sorghum hybrids.